Hemoglobin levels and anemia evaluation among pregnant women in the remote and rural high lands of mid-western Nepal: a hospital based study - Deepak Sharma; Kapil Amgain; Prem Prasad Panta; Bishal Pokhrel (BMC Pregnancy and Childbirth, 2020)
Abstract Background Anemia though is a major risk factor for unfavorable pregnancy outcomes; no previous studies have yet described the hemoglobin (Hb) concentrations and anemia prevalence among pregnant women of remote mid western highlands of Nepal where the aggravating factors that increase the risk of anemia are very common. In addition, the physiological adaptive Hb rise to altitude was considered in the study while evaluating anemia. Thus, our primary objectives were to study the hemoglobin levels and prevalence of anemia among pregnant women of Jumla and its adjoining districts, and to assess the potential associations of hemoglobin and anemia with women’s characteristics. Methods The study was conducted in 319 singleton term non-smoker pregnant women who visited to the teaching hospital for delivery. Their blood samples were tested for Hb and related sociodemographic information was collected. One-way analysis of variance (ANOVA) and independent t-test were used to compare the mean Hb levels. Multiple linear regression model and multiple logistic regression model were used to assess the association of Hb level and anemia with pregnant women’s characteristics. The prevalence of anemia was calculated based on the altitude and pregnancy-adjusted Hb cut off value for anemia [{11+ adjustment factor (1.3)} gm./dl]. Results The overall mean hemoglobin concentration was (13.497 ± 1.64) gm/dl, ranging from 8 to 19.20 g/dl. The pregnant women Hb level showed significant association with their age (Coeff = 0.059; 95% CI: 0.011, 0.106; p = 0.015) and parity (Coeff = − 0.21; 95% CI: − 0.382, − 0.038; p = 0.017). The overall prevalence of anemia in the study population was 17.9% (57/319), which varied with age, parity and ethnicity. The disadvantaged Janajatis were more likely (OR = 4.615, 95% CI: 1.48, 14.35, p = 0.008) to have anemia compared to upper cast group. Conclusion The mean Hb concentration was high and prevalence rate of anemia was low among pregnant women in karnali zone compared to average Nepali pregnant women. Women’s age and parity were significant predictors of Hb level. Ethnicity, however, was associated with the occurrence of anemia.